2018
DOI: 10.5713/ajas.17.0619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gelidium amansii extracts on in vitro ruminal fermentation characteristics, methanogenesis, and microbial populations

Abstract: ObjectiveGelidium amansii (Lamouroux) is a red alga belonging to the family Gelidaceae and is commonly found in the shallow coasts of many East Asian countries, including Korea, China, and Japan. G. amansii has traditionally been utilized as an edible alga, and has various biological activities. The objective of this study was to determine whether dietary supplementation of G. amansii could be useful for improving ruminal fermentation.MethodsAs assessed by in vitro fermentation parameters such as pH, total gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…with EFE. VFA are the principal source of energy in ruminants and they reflect the metabolic activity in the rumen (Lee et al, 2018). In this study, EFE1 at medium dose increases the production of volatile fatty acids by 21%.…”
Section: Discussionsmentioning
confidence: 62%
“…with EFE. VFA are the principal source of energy in ruminants and they reflect the metabolic activity in the rumen (Lee et al, 2018). In this study, EFE1 at medium dose increases the production of volatile fatty acids by 21%.…”
Section: Discussionsmentioning
confidence: 62%
“…This concern is particularly important when comprehensive approaches, such as meta-analyses, are used for in vitro gas production and/or digestibility studies. Indeed, a recent meta-analysis of in vitro techniques indicated issues with these techniques for measuring gas and methane production and suggested “greater harmonization of analytical procedure” to improve our understanding of the results [28,29]. A previous study by Johnson [1] indicated the importance of the rumen inoculum from animals offered different forages when examining forage digestion in vitro , and more recently, excellent reviews have highlighted the critical requirements for in vitro studies [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E. stolonifera contains polyphenolic compounds that have been suggested to deter the grazing and growth of the seaweed’s predators [7]. However, a few studies reported that algae have potential effect on rumen fermentation characteristics and methane reduction [8,9]. Identification of feed additives that can modify the rumen microbial system to manipulate ruminal fermentation characteristics and increase the efficiency of feed utilization is an effective strategy for inhibiting ruminal methanogenesis for reducing methane emissions without an adverse effect on rumen function.…”
Section: Introductionmentioning
confidence: 99%